The profile of an intuitive decision maker and the use of intuition in decision-making practice = Profil intuicyjnego decydenta a wykorzystanie intuicji w praktyce podejmowania decyzji - Malewska, Kamila (Zielona Góra: Faculty of Economics and Management Press)
The aim of this paper is to determine the relationship between the personality traits identified in the literature as characteristic of an intuitive decision-maker and the use of intuition in the decision making process. In order to empirically verify this issue, the author conducted a pilot study.
Keywords: intuicja; podejmowanie decyzji; profil intuicyjnego decydenta; intuition; decision-making; decision-maker profile